Strategic Effects of Regulatory Capital Requirements in Imperfect Banking Competition - Eva Schliephake; Roland Kirstein (Verein für Socialpolitik, 2010)
This paper analyzes the competitive effects of the Basel II Standard Approach capital requirement regulation on an oligopolistic credit market. We define the general goal of the capital regulation to be the improvement of the banking system's soundness. As in the standard literature, we assume that at least in the short-run, an adjustment of equity to the regulatory requirement may prove costly. The immediate effect of increasing the capital requirements is, thus, likely to be a reduction in the total supply of loans, and accordingly, an increase in the credit interest rate. This cost effect alone, would leave Bertrand oligopo-ly profits unchanged. Yet, we focus on an additional effect of a regulatory capital require-ment that arises because a binding requirement changes the sequence in which the strateg-ic pricing decisions are made. Assuming that short term recapitalization of a bank may prove to be costly we consider capital requirement regulation to temporarily constrain the bank's lending activities. The oligopolistic pricing competition is, therefore, transformed into a two stage capacity-pricing game à la Kreps and Scheinkman (1983). In a first stage banks choose the long-term structure of refinancing their assets, thereby making an imper-fectly binding commitment to the loan capacity as a function of the chosen degree of capitalization and the regulatory capital requirement. In the second stage, loan price com-petition takes place. It is shown that capital requirement regulation may not only decrease the supply of credit through an increased marginal cost effect but also can have a sponta-neous collusive effect resulting in even higher credit prices and increased profits for the banks.
Keywords: G21; K23; L13; 330; banking regulation; capital requirements; oligopoly; capacity constraint